Families of patients with premature coronary heart disease: an obvious but neglected target for primary prevention. Issue 7618 (6th September 2007) - Chow, C K; Pell, A C H; Walker, A; O'Dowd, C; Dominiczak, A F; Pell, J P
Abstract : Risk of premature coronary heart disease is increased in the families of affected patients. C K Chow and colleagues argue that targeting relatives for primary prevention would be an effective policy